Application of photoresponse asymmetric nanofluid film in reverse electrodialysis power generation

By using the photoresponsive asymmetric nanofluid film formed by functionalized GO sheets and MoS2/CdS nanowire stacks in reverse electrodialysis, the problems of insufficient ion selectivity and low flux of existing film materials are solved, and efficient salinity gradient power conversion and stability are achieved.

CN119656870AActive Publication Date: 2025-03-21HEILONGJIANG UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411933122.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-21
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing ion selective membrane materials have problems such as insufficient ion selectivity and low ion flux in reverse electrodialysis, resulting in low output power.

Method used

The photoresponsive asymmetric nanofluid film formed by functionalized GO sheets and MoS2/CdS nanowire stacks were prepared by vacuum suction filtration and heat treatment, and the ion flux and selectivity were improved using its two-dimensional and three-dimensional channel structures.

Benefits of technology

It realizes high-performance salinity gradient power conversion, improves the ability and efficiency of permeability energy conversion, reduces the phenomenon of concentration polarization, and has good stability and a wide range of application.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119656870A_ABST
    Figure CN119656870A_ABST
Patent Text Reader

Abstract

The invention relates to an application of a photoresponse asymmetric nanofluid film in reverse electrodialysis power generation. The invention belongs to the field of nanofluid films. The invention aims to solve the technical problems of insufficient ion selectivity and low ion flux of the existing ion selective membrane. The fluid film is formed by stacking a film layer with a two-dimensional channel and a film layer with a three-dimensional channel, the film layer is formed by stacking a layer of functionalized GO sheets, the film layer is formed by stacking a layer of one-dimensional MoS2 / CdS nanowires, the two film layers are different in electric quantity, part of pore channels are communicated, and the pore diameters are different. The fluid film is applied to a light-assisted or non-light-assisted salinity gradient energy power generation system and shows excellent performance. In addition, the fluid membrane disclosed by the invention has practical application value, and sustainable electric power is provided for small-sized electronic equipment by the series configuration of the integrated asymmetric nano fluid membrane osmotic energy batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of nanofluid membranes, and in particular relates to application of a light-responsive asymmetric nanofluid membrane in reverse electrodialysis power generation. Background Art

[0002] The huge osmotic energy generated by the salinity gradient between seawater and river water is a very promising blue energy source that can be extracted through reverse electrodialysis (RED) and used as power supply in IoT sensors, small portable devices and maritime rescue systems. The key part of RED is the ion-selective membrane material. Nanofluid membranes with unique ion transport kinetics can achieve high-performance salinity gradient power conversion.

[0003] However, existing ion exchange membranes are limited in the field of osmotic energy conversion due to their high internal resistance. Current membrane materials have problems with insufficient ion selectivity and low ion flux, resulting in low output power of membrane materials. Therefore, it is of great significance to study how to regulate ion transport and then improve the osmotic energy conversion capacity and efficiency. Summary of the invention

[0004] The purpose of the present invention is to solve the technical problems of insufficient ion selectivity and low ion flux of existing ion selective membranes, and to provide an application of a light-responsive asymmetric nanofluid membrane in reverse electrodialysis power generation.

[0005] The technical solution of the present invention is as follows:

[0006] One of the purposes of the present invention is to provide a light-responsive asymmetric nanofluid membrane, which is composed of a membrane layer with two-dimensional channels formed by stacking a layer of functionalized GO sheets and a membrane layer with three-dimensional channels formed by stacking a layer of one-dimensional MoS2 / CdS nanowires. The two membrane layers have different charges, some pores are interconnected, and the channel sizes are different.

[0007] It is further defined that the functionalized GO sheet is a GO sheet modified by carboxylated cellulose.

[0008] It is further defined that in the MoS2 / CdS nanowires, MoS2 is loaded on the surface of CdS.

[0009] It is further defined that the pore size of the membrane layer having three-dimensional channels is 10-200 nm.

[0010] It is further defined that the two-dimensional channel gap of the membrane layer having the two-dimensional channel is 0.5-10 nm.

[0011] It is further defined that the nanofluid film thickness is 10-30 μm.

[0012] The second object of the present invention is to provide a method for preparing a light-responsive asymmetric nanofluid film, the method being carried out according to the following steps:

[0013] S1: mixing the carboxylated cellulose solution and the GO dispersion evenly to obtain a functionalized GO dispersion;

[0014] S2: Sodium molybdate solution, cadmium nitrate solution and thiourea solution are mixed, the pH value is adjusted to alkaline, and then transferred to a hydrothermal reactor for hydrothermal reaction. After the reaction is completed, the product is washed to obtain MoS2 / CdS nanowires, and then the product is redispersed in deionized water to obtain a MoS2 / CdS nanowire dispersion;

[0015] S3: The MoS2 / CdS nanowire dispersion is fixed on the surface of the base film by suction filtration to form a membrane layer with three-dimensional channels, and then the functionalized GO dispersion is fixed on the surface of the membrane layer with three-dimensional channels by suction filtration to form a membrane layer with two-dimensional channels. The vacuum filtration is continued for 1-5 days, and then heat treatment is performed to obtain a light-responsive asymmetric nanofluid membrane.

[0016] It is further defined that the concentration of the carboxylated cellulose solution in S1 is 0.01-0.06 wt %, and the concentration of the GO dispersion is 0.05-0.15 wt %.

[0017] It is further defined that the volume ratio of the carboxylated cellulose solution to the GO dispersion in S1 is 4:(4-5).

[0018] It is further defined that the molar ratio of sodium molybdate to cadmium nitrate and thiourea in S2 is 1:(5-10):(35-40).

[0019] It is further defined that the molar concentrations of the sodium molybdate solution, cadmium nitrate solution and thiourea solution in S2 are 0.005-0.01 mol / L, 0.05-0.1 mol / L and 0.2-0.5 mol / L, respectively.

[0020] It is further defined that the hydrothermal reaction temperature in S2 is 100-200°C and the reaction time is 12-48h.

[0021] It is further defined that the concentration of the MoS2 / CdS nanowire dispersion in S2 is 0.05-0.15 wt%.

[0022] It is further defined that the heat treatment temperature in S3 is 60-200° C., the time is 2-12 hours, and the atmosphere is air, nitrogen or argon.

[0023] The third object of the present invention is to provide a light-responsive asymmetric nanofluid membrane for use as a salinity difference battery separator.

[0024] A fourth object of the present invention is to provide an application of a light-responsive asymmetric nanofluid membrane in a light-coupled salt difference energy power generation system.

[0025] The fifth object of the present invention is to provide a micro-osmosis energy conversion system for efficient power generation, wherein the system uses the above-mentioned light-responsive asymmetric nanofluid membrane as a diaphragm, and the two sides of the diaphragm are electrolyte solutions with concentration differences. The membrane layer with two-dimensional channels faces the high-concentration solution side, and the illuminated side is a membrane layer with three-dimensional channels formed by stacking one-dimensional MoS2 / CdS nanowires.

[0026] It is further defined that the electrolyte on both sides of the separator is the same.

[0027] It is further defined that the electrolyte is KCl, NaCl, MgCl2, LiCl or CaCl2.

[0028] It is further defined that the pH of the electrolyte solution is 3-10.

[0029] It is further defined that the concentration difference of the electrolyte solution on both sides of the separator is 5-500 times.

[0030] It is further defined that the electrode is a silver / silver chloride electrode, a copper electrode or a titanium-based ruthenium-coated electrode.

[0031] It is further defined that the light source is AM1.5, natural light, full light, ultraviolet light, visible light or near infrared light.

[0032] Further defined, the power of the light is 50-600mW / cm 2 , duration is 5min-24h.

[0033] Compared with the prior art, the present invention has the following advantages:

[0034] (1) In the present invention, the one-dimensional MoS2 / CdS nanowire membrane has three-dimensional nanochannels, which can reduce membrane resistance and improve ion flux; in addition, it can better match the two-dimensional channels formed by GO to form an asymmetric nanopore nanofluid membrane, reducing the concentration polarization phenomenon. In addition, the asymmetric nanopore nanofluid membrane can effectively utilize sunlight to achieve high-performance osmotic energy conversion.

[0035] (2) The method for preparing the asymmetric nanofluid membrane provided by the present invention only uses a vacuum filtration method, which is simple to operate and avoids the shortcomings of the prior art of complex preparation process, high cost and poor controllability.

[0036] (3) The asymmetric nanofluid membrane of the present invention has obvious advantages in the application as a salt difference battery diaphragm and a light-coupled salt difference energy generation system. It allows cations to selectively pass under different pH conditions, and the asymmetric nanochannel has an ion diode effect, thereby reducing the concentration polarization effect, which is beneficial to the improvement of ion transmission efficiency; at the same time, the energy conversion efficiency is high and the application range is wide: it can be used in electrolyte solutions with pH = 3-11 and different electrolyte solutions. In addition, it also has high stability. The salt difference energy generation system containing the asymmetric nanofluid membrane also has good stability. After 1 month of continuous testing, its power generation efficiency has no obvious attenuation.

[0037] (4) With practical application value, the series configuration of the integrated asymmetric nanofluid membrane osmotic energy cells provides sustainable power for small electronic devices. BRIEF DESCRIPTION OF THE DRAWINGS

[0038] Figure 1 is a cross-sectional scanning electron microscope image of the asymmetric nanofluid membrane in Example 1;

[0039] Figure 2 is the zeta potential diagram of functionalized GO and MoS2 / CdS;

[0040] Figure 3 This is a diagram of the system for converting salt difference energy into electrical energy according to the present invention;

[0041] Figure 4 is a graph showing the relationship between power generation density and external resistance in Example 2;

[0042] Figure 5 The relationship between the power generation density and the external resistance at 5 and 500 times the salinity gradient in Example 3;

[0043] Figure 6 It is the power density diagram of power generation under different pH in Example 4;

[0044] Figure 7 is a graph of power generation density under different electrolytes in Example 5;

[0045] Figure 8 is a diagram of power generation density under different incident light in Example 6;

[0046] Fig. 9 2 is a diagram of power generation density under different test areas in Example 7. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0048] The experimental methods used in the following examples are conventional methods unless otherwise specified. The materials, reagents, methods and instruments used are conventional materials, reagents, methods and instruments in the art unless otherwise specified, and can be obtained through commercial channels by those skilled in the art.

[0049] The terms "comprising," "including," "having," "containing," or any other variations thereof, as used in the following examples, are intended to cover a non-exclusive inclusion. For example, a composition, step, method, article, or apparatus comprising the listed elements is not necessarily limited to only those elements, but may include other elements not expressly listed or inherent to such composition, step, method, article, or apparatus.

[0050] When equivalent, concentration or other value or parameter is represented by the range limited by range, preferred range or a series of upper preferred value and lower preferred value, this should be understood as specifically disclosing all ranges formed by any pairing of any upper range limit or preferred value and any lower range limit or preferred value, regardless of whether the scope is disclosed separately. For example, when disclosing range "1 to 5", described range should be interpreted as including range "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5" etc. When numerical range is described in this article, unless otherwise stated, the scope is intended to include its end value and all integers and fractions within the scope. In the present application specification and claims, range limitation can be combined and / or interchanged, if these ranges are not otherwise stated, include all sub-ranges contained therein.

[0051] The indefinite articles "a" and "an" before the elements or components of the present invention have no limitation on the quantity requirements (i.e. the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted as including one or at least one, and the elements or components in the singular form also include the plural form, unless the quantity obviously refers to the singular form only.

[0052] The "one embodiment" or "embodiment" of the present invention refers to a specific feature, structure or characteristic that can be included in at least one implementation of the present invention. The "in one embodiment" that appears in different places in this specification does not refer to the same embodiment, nor is it a separate or selective embodiment that is mutually exclusive with other embodiments.

[0053] The endpoints and any values ​​of the ranges disclosed in the invention are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be regarded as specifically disclosed in this article.

[0054] Example 1. Preparation of photoresponsive asymmetric nanofluid film

[0055] (1) dissolving TEMPO system oxidized carboxylated cellulose (TOCNF) in deionized water to prepare a carboxylated cellulose solution having a carboxylated cellulose content of 0.05 wt %;

[0056] Dispersing GO in deionized water to prepare a GO dispersion with a GO content of 0.1 wt%;

[0057] 4 mL of carboxylated cellulose solution and 18 mL of GO dispersion were mixed and stirred evenly to obtain a functionalized GO dispersion;

[0058] (2) dissolving 0.48 mmol sodium molybdate, 3.46 mmol cadmium nitrate and 18.01 mmol thiourea in 60 mL deionized water to obtain a mixed solution;

[0059] The mixed solution was adjusted to a pH value of 11, and then transferred to a hydrothermal reactor for a hydrothermal reaction at 200° C. for 24 h. After the reaction was completed, it was naturally cooled to room temperature. The product was washed with deionized water and ethanol in turn to remove unreacted raw materials and by-products, and the MoS2 / CdS nanowires were obtained by centrifugation and filtration.

[0060] Dispersing MoS2 / CdS nanowires in deionized water to obtain a dispersion of MoS2 / CdS nanowires with a concentration of 0.1 wt%;

[0061] (3) 20 mL of MoS2 / CdS nanowire dispersion was fixed on the surface of a polycarbonate filter membrane with a pore size of 0.1 μm by suction filtration to form a membrane layer with a pore size of 10-200 nm and a three-dimensional channel. Then 22 mL of functionalized GO dispersion was fixed on the surface of a three-dimensional porous membrane by suction filtration to form a membrane layer with a two-dimensional channel gap of 0.5-10 nm. The membrane was then vacuum filtered for 2 days and then heat treated in an oven at 60 °C for 2 h. Figure 1 As shown, a photoresponsive asymmetric nanofluid film with a thickness of 10 μm was obtained.

[0062] from Figure 2 It can be seen that the functionalized GO maintains a high negative charge in a wide pH range, while MoS2 / CdS carries a smaller amount of negative charge, indicating that the photoresponsive asymmetric nanofluid film has a charge asymmetric characteristic.

[0063] Example 2: Salt difference can be converted into electrical energy

[0064] like Figure 3As shown, the device for converting salt difference into electrical energy is a closed system, with 0.5M NaCl electrolyte solution in the left container and 0.01M NaCl electrolyte solution in the right container. The electrodes are silver / silver chloride electrodes. The light-responsive asymmetric nanofluid membrane prepared in Example 1 is installed in the middle of the two containers and fixed with screws. The test area is 28mm 2 The small pore end (functionalized GO membrane) faces the high concentration solution side, while the large pore end (MoS2 / CdS membrane) faces the low concentration solution side. The two electrolyte solutions are connected through an external ammeter and a load resistor. The pH of the electrolyte solution is adjusted to 7, and the corresponding external circuit energy density is 0.142W / m 2 , under simulated sunlight, the light intensity is 100mW / cm 2 , the results are as follows Figure 4 As shown, the energy density in the external circuit is increased to 0.253W / m 2 Compared with no illumination, the power density is increased by 78.2%.

[0065] Example 3: Salt difference can be converted into electrical energy under different salinity gradients

[0066] Compared with Example 1, by changing the concentration gradient of the NaCl solution and keeping other conditions unchanged, the influence of different salt solution concentration gradients on the energy density in the external circuit was tested. When the salt solution concentration gradients were 5 and 500, the corresponding external circuit energy densities were 0.032 and 0.838 W / m 2 , respectively 69.9% and 86.6% higher than when there was no light.

[0067] The results are as follows Figure 5 As shown, combined with the results of Example 1, it can be found that when the salt solution concentration gradient is 500, the efficiency of converting salt difference energy into electrical energy is the highest.

[0068] Example 4: Converting salt difference energy into electrical energy using light-responsive asymmetric nanofluid membranes at different pH values

[0069] Compared with Example 1, the pH of the electrolyte solution was adjusted to 3, 5, 9 and 10 respectively. It was found that the energy density in the external circuit was 0.146 W / m 2 , 0.15W / m 2 , 0.153W / m 2 and 0.17W / m 2 . Under simulated sunlight, the light intensity is 100mW / cm 2 , the energy density is increased to 0.222W / m 2 、0.248W / m 2 , 0.293W / m 2and 0.339W / m 2 .

[0070] The results are as follows Figure 6 As shown in the figure, combined with the results of Examples 1-2, it is shown that when the pH of the electrolyte solution is 10, it has the maximum energy conversion efficiency and the external circuit energy density is 0.339 W / m 2 .

[0071] Example 5: Converting salt difference energy into electrical energy using light-responsive asymmetric nanofluid membranes in different electrolytes

[0072] Compared with Example 1, the solutes of the electrolyte solution were replaced with LiCl, KCl, CaCl2 and MgCl2 respectively, with the concentrations unchanged. The results showed that the energy density in the external circuit was 0.088 W / m 2 , 0.169W / m 2 、0.087W / m 2 and 0.050W / m 2 . Under simulated sunlight, the light intensity is 100mW / cm 2 , the energy density is increased to 0.171W / m 2 , 0.317W / m 2 , 0.160W / m 2 and 0.098W / m 2 .

[0073] The results are as follows Figure 7 As shown in the figure, combined with the results of Examples 1-2, it is shown that when the electrolyte is KCl solution, it has the highest energy conversion efficiency and the external circuit energy density is 0.317 W / m 2 .

[0074] Example 6: Photoresponsive asymmetric nanofluid membranes under different incident light conditions convert salt difference energy into electrical energy

[0075] Compared with Example 1, under incident light of 420nm and 500nm, the light intensity is 100mW / cm 2 The results show that the energy density in the external circuit is 0.274W / m 2 and 0.265W / m 2 .

[0076] The results are as follows Figure 8 As shown in the figure, combined with the results of Example 1-2, when the incident light is 420nm, the light intensity is 100mW / cm 2 , has the highest energy conversion efficiency, and the external circuit energy density is 0.274W / m -2 .

[0077] Example 7: Photoresponsive asymmetric nanofluid membranes with different test areas convert salt difference energy into electrical energy

[0078] Compared with Application Example 1, the light intensity is adjusted to 100mW / cm 2 The test areas are 0.03, 3.14, 7, 12.56, 19.6, 50, and 78.5 mm 2 and 113mm 2 When the corresponding external circuit energy density is: 43.8W / m 2 , 0.296W / m 2 、0.224W / m 2 , 0.160W / m 2 、0.143W / m 2 , 0.128W / m 2 , 0.116W / m 2 and 0.118W / m 2 Under simulated sunlight, the light intensity is 100mW / cm 2 , the energy density is increased to 59.5W / m 2 、0.584W / m 2 、0.450W / m 2 , 0.339W / m 2 , 0.299W / m 2 , 0.237W / m 2 、0.186W / m 2 and 0.184W / m 2 .

[0079] The results are as follows Fig. 9 As shown in the figure, combined with the results of Examples 1-2, it is shown that as the test area increases, the energy conversion efficiency decreases and tends to be stable. When the test area increases by 113 mm 2 At this time, the energy density in the external circuit can still be as high as 0.184W / m 2 .

[0080] Example 8: Stability test of salt difference energy power generation system

[0081] The system of Example 1 was continuously tested, and the results showed that the pH of the electrolyte solution was 7, and without the addition of an electrolyte, the current did not decay after 12 hours of IT test curve. And after 1 month of testing, its power generation efficiency did not decline.

[0082] Tests have shown that under different lighting conditions, the salt difference energy generation system containing the photoresponsive heterogeneous nanofluid membrane has stable current output performance and energy conversion efficiency.

[0083] In summary, it can be seen that the one-dimensional MoS2 / CdS nanowire membrane in the asymmetric nanofluid membrane of the present invention has a three-dimensional nanochannel, which can reduce membrane resistance and improve ion flux; in addition, it can better match the two-dimensional channel formed by GO to form an asymmetric nanopore nanofluid membrane, which reduces the concentration polarization phenomenon. It has obvious advantages in the application as a salt difference battery separator and a light-coupled salt difference energy generation system. It allows cations to pass selectively under different pH conditions, and the asymmetric nanochannel has an ion diode effect, thereby reducing the concentration polarization effect, which is conducive to the improvement of ion transmission efficiency; at the same time, the energy conversion efficiency is high and the application range is wide: it can be used in electrolyte solutions with pH = 3-11 and different electrolyte solutions. In addition, it also has high stability. The salt difference energy generation system containing the asymmetric nanofluid membrane also has good stability. After 1 month of continuous testing, its power generation efficiency has no obvious attenuation. In addition, more importantly, the asymmetric nanofluid membrane of the present invention has practical application value, and the series configuration of the integrated asymmetric nanofluid membrane osmotic energy battery provides sustainable power for small electronic devices.

[0084] The above are only preferred specific embodiments of the present invention, which are all different implementations based on the overall concept of the present invention, and the protection scope of the present invention is not limited thereto. Any changes or substitutions that can be easily thought of by a person skilled in the art within the technical scope disclosed by the present invention should be included in the protection scope of the present invention. Therefore, the protection scope of the present invention should be based on the protection scope of the claims.

Claims

1. A light-responsive asymmetric nanofluid film, characterized in that: The nanofluid membrane is composed of a membrane layer with two-dimensional channels formed by stacking a layer of functionalized GO sheets and a membrane layer with three-dimensional channels formed by stacking a layer of one-dimensional MoS2 / CdS nanowires. The two membrane layers have different charges, some pores are interconnected, and the channel sizes are different.

2. The nanofluid membrane according to claim 1, characterized in that: The functionalized GO sheets are GO sheets modified by carboxylated cellulose, and the MoS2 in the MoS2 / CdS nanowires is loaded on the surface of CdS.

3. The nanofluid membrane according to claim 1, characterized in that The pore size of the membrane layer with three-dimensional channels is 10-200nm, the gap between the two-dimensional channels of the membrane layer with two-dimensional channels is 0.5-10nm, and the thickness of the nanofluid membrane is 10-30μm.

4. The method for preparing a nanofluid membrane according to any one of claims 1 to 3, characterized in that: The method: S1: mixing the carboxylated cellulose solution and the GO dispersion evenly to obtain a functionalized GO dispersion; S2: Sodium molybdate solution, cadmium nitrate solution and thiourea solution are mixed, the pH value is adjusted to alkaline, and then transferred to a hydrothermal reactor for hydrothermal reaction. After the reaction is completed, the product is washed to obtain MoS2 / CdS nanowires, and then the product is redispersed in deionized water to obtain a MoS2 / CdS nanowire dispersion; S3: The MoS2 / CdS nanowire dispersion is fixed on the surface of the base film by suction filtration to form a membrane layer with three-dimensional channels, and then the functionalized GO dispersion is fixed on the surface of the membrane layer with three-dimensional channels by suction filtration to form a membrane layer with two-dimensional channels. The vacuum filtration is continued for 1-5 days, and then heat treatment is performed to obtain a light-responsive asymmetric nanofluid membrane.

5. The method according to claim 4, characterized in that The concentration of carboxylated cellulose solution in S1 is 0.01-0.06wt%, the concentration of GO dispersion is 0.05-0.15wt%, the molar ratio of sodium molybdate to cadmium nitrate and thiourea in S2 is 1:(5-10):(35-40), and the concentration of MoS2 / CdS nanowire dispersion in S2 is 0.05-0.15wt%.

6. The method according to claim 4, characterized in that The hydrothermal reaction temperature in S2 is 100-200°C and the time is 12-48h, and the heat treatment temperature in S3 is 60-200°C and the time is 2-24h.

7. Use of the nanofluid membrane according to any one of claims 1 to 3 as a separator for a salt difference battery.

8. Use of the nanofluid membrane according to any one of claims 1 to 3 in a light-coupled salt difference energy power generation system.

9. A micro-osmosis energy conversion system for efficient power generation, characterized in that: The system uses the light-responsive asymmetric nanofluid membrane described in any one of claims 1 to 3 as a diaphragm, with electrolyte solutions with concentration differences on both sides of the diaphragm, a membrane layer with two-dimensional channels facing the high-concentration solution side, and a membrane layer with three-dimensional channels formed by stacking one-dimensional MoS2 / CdS nanowires on the illuminated side.

10. The system according to claim 9, characterized in that The electrolytes on both sides of the diaphragm are the same, the concentration difference of the electrolyte solution on both sides of the diaphragm is 5-500 times, the pH of the electrolyte solution is 3-10, and the power of the light is 50-600mW / cm 2 , duration is 5min-24h.

Citation Information

Patent Citations

  • Simple preparation method of cadmium vanadate monocrystalline nanometer wire

    CN105970281A

  • Oxidized molybdenum disulfide -graphene oxide composite nanofiltration membrane and preparation method thereof

    CN113797775A

  • Nanofluid photoelectric energy conversion Schottky heterogeneous film and preparation method and application thereof

    CN118632545A

  • COF / GO / ANF composite nano-channel membrane and super-assembly preparation method thereof

    CN118988000A

  • Ion-Selective Composite Membrane

    US20230226499A1